The Effect of Financial Compensation, Work Discipline and NonPhysical Work Environment on Employee Productivity - Sinta Sundari Heriyanti; Melyana Dwi R Santi (Journal of Research in Business, Economics, and Education, 2020)
Work productivity is a very important factor in supporting the success of the company's business in all aspects. Employee work productivity will continue to increase if employees are always disciplined and follow every company rule and there is a good work environment. As for the problem in this study is a decrease in employee productivity at PT. Furukawa Automotive Systems Indonesia. This study aims to determine the effect of financial compensation, work discipline and non-physical work environment on employee work productivity at PT. Furukawa Automotive Systems Indonesia. In this study using quantitative research. Data were collected through a questionnaire method to 50 respondents. This study uses a saturated sample technique. The research was processed using multiple linear regression analysis with the SPSS 22 program. The results of this study indicate that the variables of financial compensation, work discipline and non-physical work environment have a positive and partially significant effect on the work productivity of PT. Furukawa Automotive Systems Indonesia.